Depresión y aislamiento social en personas mayores, análisis del rol de la participación tecnológica - Castillo Riquelme, Víctor (2023)
Objective. This study sought to analyze the role of technological participation of the elderly in Chile in relation to geriatric depression and social isolation. Method. A non-experimental and correlational study was conducted in which the geriatric depression scale (GDS-15), the Lubben social network scale (LSNS-6) and a battery of questions to measure technological participation were applied in a sample of 149 elderly people from central-southern Chile. Results. The results indicate the existence of a positive correlation between technological participation and perception of social support networks, particularly friendship networks, as well as a negative correlation with geriatric depression. Older people who use the Internet have lower levels of depression and a lower risk of social isolation. Conclusion. Technological participation facilitates the preservation of social ties and promotes the autonomy of the elderly, having a positive impact on the indicators of depression and isolation. However, technological participation represents a challenge for public policies due to the gaps that are manifested based on the sociocultural profile and age of the users.